Best of SIDFEx applications, with a focus on deformation forecasts ... - Ludwig, Valentin; Goessling, Helge; SIDFEx Team (Zenodo, 2023)
Topic: Presentation of the Sea Ice Drift Forecast Experiment (SIDFEx). Content: I first gave an introduction on the rationale behind and setup of SIDFEx, continued with a selection of applications and then focused on sea-ice deformation forecasts no varying spatial scales. Duration: 25 minutes. Occasion: 11th workshop of the International Ice Chart Working Group on Data Assimilation (IICWG-DA). Date: March 23, 2023 in Oslo ...